ЗАЛОЗНИЙ ШЛЯХ, ЛОСИЦЬКА ДОРОГА ТА ЛОЗІЄ ìСЛОВА О ПОЛКУ ІГОРЕВІМî (Zaporizhzhia Historical Review, 2021)
The article is devoted to the analysis of origin of the name and placement of Zaloznyi road and Losytskyi way, their mutual geographical position. The author gives an approval of the thought that Loziye from the ìSong of Igorís Campaignî is the mentioned Losytskyi way.